Adequate China media overview but little that challenges - Cocker, Alan (Pacific Journalism Review : Te Koakoa, 2011)

Reviewed book edited by: James F. Scotton and William A. Hachten



Publication date: May, 2011




This book argues that 'China today enjoys complex and highly advanced media through its newspapers, magazines, radio and television broadcasting, and cinema accompanied by the necessary ancillary services of advertising and public relations' (p. 207)


(untitled)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYxN2kxLjM4NQ